Feasibilty Analysis Of South Java Road Link in Jogyakarta Province - Eko Muliawan Satrio (International Conference on Coastal and Delta Areas, 2017)
Distribution of goods and services along the island of Java still mainly depends on the North Java Coastal Road named PANTURA. Trafict demands along this road are increasing every year and road capacity can not match this growth. The government of Indonesia has plans to develop another trans Java route to meet the demands and to develop the southern corridor of Java. The province of Jogyakarta will experience an impact and needs to provide input to the proposed route, as the road can support development of existing regional potencies. The objective of study is to analyze the economic feasibility of fourth alternative southern Java road route in Jogyakarta province there were evaluated. This analyzewere based on estimated producer surplus of agricultural commodities within influence area. Keyword : feasibility study, South Java road link, producer surplus, agricultural potency, Jogyakarta